A study of emotion management and identity construction in Chinese medical treatment discussions. (December 2022) - Li, Chengtuan
Based on a medical corpus, this study attempts to capture how doctors manage their emotions and construct their professional identity in treatment discussions. Using the Emotion Model and the Model of Epistemics and Deontics Gradient, I find that (1) when their professional expertise is questioned or doubted, doctors highlight their epistemic rights and displays negative emotions; (2) when their professional role is negated, doctors give the deontic rights to their patients and discharge negative emotions; and (3) when their professional ethics is challenged, doctors project their professional morality, reinforce their deontic rights and give vent to negative emotions. This study, by integrating the Confucian System of Moral Virtues (see) with Emotion Model, establishes a theoretical framework for examining the association between emotion management and identity construction in Chinese medical discourse.